Pengaruh Harga, Review Produk, Jaminan Keamanan Terhadap Keputusan Pembelian Produk Pada Situs Jual Beli Online Shopee - Jenni Veronika Br Ginting; Chairia Chairia; Polin Ramles (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Modern markets are no longer run by way of face-to-face transactions, modern markets are now using an online system where by using a mobile or desktop application-based system, you can apply the system in terms of buying and selling, this is commonly called e-commerce, one of which is e-commerce. one e-commerce that is very popular among the people of Indonesia, namely shopee because there are so many shopee users, a lot of business people start trading on the shope application, the process of trade competition is getting tougher day by day they have to build and see what opportunities can increase business activities and achievement of business targets. It is important to know the influence of buyers' decisions on online shopping at shope to find out good targets and targets in increasing the quality and quantity of buying and selling online. In this study, we want to know the effect of price, product reviews and security guarantees as independent variables on product purchasing decisions. It was found that prices, product reviews and purchase safety have an important role and have a positive effect on product purchasing decisions at shopee.